Erin Riner: capstone - Riner, Erin, artist (Colorado State University. Libraries, 2019)
The artist's statement: I really focus on the application of the paint and how I could be more loose with not only colors, but also with the way I placed the paint. Some of my paintings have a figurative reference to it while my most recent pieces have and absence of the figure. One of my Inspirations that propelled my desire to leave the figure out was Helen Frankenthaler's Blue Lady. Just like Frankenthaler, I suggest a subtle dance of colors throughout each piece. My earlier works containing the figure suggest the idea of distancing myself from my own social role, where the painting I create of myself is one on its own. Instead of self expression and telling stories of myself through predisposed ideas I have of who I am, I let the paintings speak for themselves and allow myself to be open to what they have to tell me about who I am after I have finished the piece. After some time and reflection with the work, I can conclude as of now that there is an underlying meaning of myself changing and evolving where I can see areas of my past and present to be evident. The intent behind each painting is left up to the viewer, that being said, there is no underline, predisposed meaning thus creating an open experience for each individual. Some may relate my recent works to water while others might suggest references to patterns in the sky or space. From the beginning, my work has never felt forced. Going in with just the idea of creating a work of art creates a process and experience for me like none other. These paintings were made with the absence of anxiety that came with trying to represent a specific object or figure. By using a different medium (enamel) I was able to create layer upon layer. The application process was crucial in creating the final pieces that the viewer experiences. Just as the shades of blue dance around the canvas, so did I in creating them. From one side to another, I would move my body and arms in variations of speeds to create the illusion of fast and slow moving blue.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting